Tet Enzymes, Variants, and Differential Effects on Function - Melamed, Philippa; Yosefzon, Yahav; David, Cfir; Tsukerman, Anna; Pnueli, Lilach (Frontiers in Cell and Developmental Biology, 2018)
Discovery of the ten-eleven translocation 1 (TET) methylcytosine dioxygenase family of enzymes, nearly 10 years ago, heralded a major breakthrough in understanding the epigenetic modifications of DNA. Initially described as catalyzing the oxidation of methyl cytosine (5mC) to hydroxymethyl cytosine (5hmC), it is now clear that these enzymes can also catalyze additional reactions leading to active DNA demethylation. The association of TET enzymes, as well as the 5hmC, with active regulatory regions of the genome has been studied extensively in embryonic stem cells, although these enzymes are expressed widely also in differentiated tissues. However TET1 and TET3 are found as various isoforms, as a result of utilizing alternative regulatory regions in distinct tissues. Some of these isoforms, like TET2, lack the CXXC domain which probably has major implications on their recruitment to specific loci in the genome, while in certain contexts TET1 is seen paradoxically to repress transcription. In this review we bring together these novel aspects of the differential regulation of these Tet isoforms and the likely consequences on their activity.